2007
DOI: 10.3181/0609-rm-218
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Epithelial Cells Treated Concurrently with TGF-α and TGF-β Exhibit Enhanced Proliferation and Death

Abstract: Transforming growth factor-a (TGF-a) stimulates while TGF-b inhibits mammary epithelial cell growth, suggesting that when cells are treated concurrently with the growth factors their combined effects would result in no net growth. However, combined treatments stimulate proliferation and cellular transformation in several cell lines. The objective of this paper was to describe the effect of long-term (6 days) concurrent TGF-a and TGF-b treatment on normal mammary epithelial cell growth pattern, morphology, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…We hypothesized that the roles of TGF-β1 in mammary involution were to regulate ECM remodeling and stimulate turnover of cell populations. These roles are supported by in vitro and in vivo findings, which showed that addition of TGF-β1 to epithelial cells stimulates synthesis of ECM proteins and inhibits epithelial cell growth (Silberstein and Daniel, 1987;Musters et al, 2004;Casey et al, 2007) and that the expression of TGF-β1 mRNA increases in rodent and bovine mammary gland (both pregnant and nonpregnant) after the initiation of involution (Plath et al, 1997;Faure et al, 2000;Bierie et al, 2009).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We hypothesized that the roles of TGF-β1 in mammary involution were to regulate ECM remodeling and stimulate turnover of cell populations. These roles are supported by in vitro and in vivo findings, which showed that addition of TGF-β1 to epithelial cells stimulates synthesis of ECM proteins and inhibits epithelial cell growth (Silberstein and Daniel, 1987;Musters et al, 2004;Casey et al, 2007) and that the expression of TGF-β1 mRNA increases in rodent and bovine mammary gland (both pregnant and nonpregnant) after the initiation of involution (Plath et al, 1997;Faure et al, 2000;Bierie et al, 2009).…”
Section: Discussionmentioning
confidence: 74%
“…This observation was somewhat surprising in light of our hypothesis. In previous studies, we showed that 5 ng/mL TGF-β1 inhibited mouse mammary epithelial cell growth, in part through arresting cells in G 1 /G 0 (Casey et al, 2007). Exogenous TGF-β1 implanted in mammary glands of prepubertal mice also inhibited epithelial cell proliferation in end buds (Silberstein and Daniel, 1987).…”
Section: Discussionmentioning
confidence: 82%
“…The influence of TGF-, a member of the epidermal growth factor family of peptides, on breast cancer incidence is not fully explored. However, a previous laboratory study has demonstrated that TGF-enhances the growth of normal mouse mammary epithelial cell line (Casey et al, 2007). Furthermore, TGF-can act as a mitogen and differentiation factor in mammary epithelium inducing multifocal hyperplastic and malignant lesions in an animal model (Smith et al, 1995).…”
Section: Epidermal Growth Factorsmentioning
confidence: 99%
“…The balance between the two pathways determines the net result. TGF-exerts its protective effect against breast cancer by inducing cell cycle arrest and promoting apoptosis of normal mammary epithelial cells (Casey et al, 2007). Data from 6,703 cases and 6,840 controls have been assessed in a recent meta-analysis performed by Scollen and colleagues in attempt to better understand the association between TGF-and breast cancer risk (Scollen et al, 2011).…”
Section: Genes Expression In Breast Tissue Associated To Mammographicmentioning
confidence: 99%
“…It is localized to the developing stroma and the epithelial bud. TGF-b is seen in the ECM throughout prenatal development where it modulates cell-ECM interaction [35] , inhibiting cell proliferation [102,159,186,187] . BM inhibits the expression of TGF-b [188] .…”
Section: Genes Transcription Factors and Growth Factors During Prenamentioning
confidence: 99%